Gambaran Kadar Hb Pada Penderita Malaria Tropika di UPTD Puskesmas Kuala Makmur - Manihuruk, Fani Nuryana; Akrama, Nurul (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Malaria is an infectious disease caused by Plasmodium falciparum. In people with malaria, Plasmodium attacks red blood cells. Malaria parasite infection destroys red blood cells, so the blood of malaria sufferers is always much lower than normal hemoglobin levels. Parasitic red blood cells can be destroyed by phagocytes trying to overcome this parasitic infection. The degree of anemia in malaria patients can affect the severity of the disease and also affect treatment efforts. This study used the POCT method or strip test with the Easy Touch device. This study aims to determine hemoglobin levels in malaria patients at the Kuala Makmur Public Health Center, Simeulue Regency in 2022 based on age, gender, and degree of anemia. The number of samples examined as many as 25 were taken by accidental sampling. The type of research used is quantitative research, that is, the type of research conducted with the aim of looking at the description of hemoglobin levels in patients with tropical malaria caused by Plasmodium falciparum. The results showed that the highest incidence of tropical malaria occurred in patients aged 21-30, female sex with normal degree of anemia 40%, mild 28%, moderate 12% and severe 20%. The average hemoglobin level in malaria patients is below normal with a percentage of 68%. From the results of the study, it can be concluded that hemoglobin levels in tropical malaria patients in the working area of ​​UPTD Puskesmas Kuala Makmur are below normal. Suggestions for health workers are expected to provide more frequent counseling about malaria about the meaning, symptoms, methods of prevention, modes of transmission, and treatment. For patients, so that patients check themselves more quickly if they have a fever and take anti-malarial drugs according to the instructions recommended by health workers.